Automated CO2 angiography: Injection pressure and volume settings. (June 2020) - Corazza, Ivan; Sapignoli, Sonia; Cercenelli, Laura; Marcelli, Emanuela; Faggioli, Gianluca; Gargiulo, Mauro; Stella, Andrea; Diemberger, Igor; Rossi, Pier Luca; Zannoli, Romano
Highlights: Angiography with CO2 as contrast medium is a really promising technique with a wide range of application. Knowledge of hemodynamic and injection parameters allows a full control of CO2 angiographic procedures. A full control of gas injection can lead to optimize the procedure reducing the pain for the patients. CO2 is a safe medium and can be used on patients with iodinated contrast medium intolerance. Abstract: The purpose of this work was to outline some practical rules for pressure and volume settings in automatic CO2 injection angiographic procedures focusing on the iliac arterial system, since, in current clinical practice, each operator uses his personal experience to obtain imaging results which are not always easy to compare. A theoretical model was thus developed and then verified by a mechanical simulator of the aortoiliac vascular system, with constant and pulsatile blood flow. The conditions of forward and reverse flows have been described, both for constant and pulsatile regimens and pressures, flows, and optical images of the bubbles in glass vessels were simultaneously acquired, analyzed and compared. Our results demonstrated that "good" radiological images (adequate to patient's conditions and clinical need) are strictly related to appropriate settings of gas injection pressure and flow, in accordance with two simple operative rules. These rules prescribe that the patient's pressure, the blood flow in the vessel, and the hydraulic resistance of the gas injection line be known: the first two parameters may be estimated, while the third must be experimentally measured. By following these rules, it is possible to obtain the best results for each clinical setting, a more standardized approach and better imaging during angiographic procedures with carbon dioxide as contrast medium.